SENDERIZACION Y SEÑALETICA TURISTICA PARA LOS ATRACTIVOS TURISTICOS “CASCADA EL AIRO” Y “QUEBRADA EL VERDUM” DE LA PARROQUIA EL TAMBO DEL CANTON CATAMAYO DE LA PROVINCIA DE LOJA - Macas Cuenca, Lidia Ximena (2016)
The tourism it focuses as sustainable development for the peoples that have reached achievements in his economies what demonstrates that the development of a country across the sustainable tourism is a reality This factor is reflected in job creation, improvement of infrastructure, introduction of basic services and the opportunity for towns that have seen tourism as an economic alternative for all the World Tourism Organization proposes the conversion of tourism in an activity that has as its main objective the economic, social and environmental balance, in other words sustainable tourism by applying the correct application of destinations El Tambo is one of the rural parishes of the canton Catamayo, is located south-east of the canton Catamayo, its temperature varies between 18 ° C and 20 ° C, consequently it keeps a climate warm to humid dry. This place is known for its beautiful scenery, varied flora, beautiful streams and magnificent waterfalls, which constitutes a paradise to be visited; From this perspective, the present study has as main objective to contribute to tourism development in the parish through of the Senderización and attractive signaling for Waterfall The Airo and Quebrada El Verdum, parish El Tambo, the canton Catamayo, Loja province; the idea is to provide a signaling system with basic information to facilitate the travel of tourists. Likewise specific objectives to provide specific information to develop appropriate work arises, for it was necessary to be raised; A diagnosis of the current situation of the Parroquia El Tambo; Propose Senderización and signage of the Attractions "Waterfall The Airo" and "Quebrada The Verdum and Socialize the proposal Senderización and attraction signage" Waterfall The Airo "and" Quebrada the Verdum "to relevant authorities. 6 The methodology used was through different methods and techniques; The bibliographic, analytical and synthetic methods used in the first objective; however was supplemented with the help of techniques such as direct observation, the same as was to conduct a quick survey, the adaptation of the matrix characterization Carla Ricaute adjusting to the reality of the parish was also performed; was also used MINTUR attractive inventory and SWOT Matrix. As for the second objective methods, inductive and deductive used; also made use of the GPS, which allowed collecting points for the design and exact map of the path coordinates; determining the load capacity Miguel Cifuentes methodology was used; and as for signage tourist signage manual MINTUR was strictly used. Finally as to the third objective MARPP technique that consisted of a participatory workshop where stakeholders participated in the socialization of the proposed senderización and signage used. As a result it was possible to make a diagnosis of the current situation of the parish El Tambo, where it was known location, boundaries, climate, flora, fauna, social and economic aspect, so it has infrastructure and attractions. Likewise the proposed senderización and signage for the two paths was performed; if the path of the proposal Cascada Airo eigth signals between informational, directional and totems and as the path of Quebrada El Verdum allowed the proposal of nine signals are left In conclusion it is considered that the parish El Tambo has natural and cultural attractions essential to boost the tourism development of the site, however these attractions need to be suitable to be put in value. It is worth mentioning that there are no access established in the parish to visit the attractions, as no signs that allow tourists guided properly, directly affecting tourism 7 The proposed senderización positively contribute to the attractiveness and its visitors, as it will contribute to the protection and conservation of the same, and also offer a quality service at the time of his visit. Among the recommendations that follow are aimed primarily at parochial GAD; It is carrying out projects that are strictly related to the tourism sector, since the parish through its attractions is rich that can be exploited with the support and contribution of all. Likewise the Gobierno Autonomy Decentralized is recommended, take the necessary steps to improve the infrastructure of tourism services, which facilitate the requirements of tourists visiting the parish and at the same time to guarantee a better quality of life for its inhabitants